Analysis of the Implementation of the Community Health Center Integrated Recording and Reporting System (SP2TP) in 2024 - Treviga Orbita Pangarindang; Dwi Yulia Maritasari; Dian Utama Pratiwi Putri (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
The Community Health Center Integrated Recording and Reporting System (SP2TP) is the main source of information for the Community Health Center Management Information System (SIMPUS). The impact of late reporting or the absence of monthly SP2TP reports is the unavailability of up to date data that can be used as accurate/relevant information for people who need it as research reference material. The phenomena that occur are delays in sending SP2TP reports by officers as well as delays in input and sending data to the Health Service which must be done on the 5th of every month. The aim of this research is to analyze the implementation of SP2TP in 2024. This type of research is qualitative with a phenomenological approach. The technique for determining informants uses Purposive Sampling with a total of 8 informants. Data collection carried out included in-depth interviews, FGDs, and observations. This research uses triangulation of sources, methods, and time. Data analysis in this research used the NVivo application. The research results show that planning and organization are quite good, but the existing human resources have multiple tasks and do not meet the qualifications, which has an impact on the timeliness of SP2TP data collection. SP2TP coordination is carried out bottom up from the bottom, namely PJ Program to PJ Health Service starting from recording data for each program and carried out using Excel. SP2TP reporting is carried out after recapitulation by the SP2TP data manager. Suggestion: Implementation of SP2TP should use Google Form or Google Spreadsheet or a special IT application for SP2TP to facilitate reporting from the Puskesmas level to the Regency/City Health Office